1963
DOI: 10.1128/jb.86.6.1275-1282.1963
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the Enterococci as Related to Their Taxonomy

Abstract: Studies on a collection of enterococci isolated from diverse sources have confirmed the existence of two distinct species, namely, Streptococcus faecalis and Streptococcus faecium. In contrast with S. faecium, S. faecalis characteristically ferments melezitose, sorbitol, glycerol (anaerobically), citrate, and gluconate; fails to ferment arabinose and melibiose; has strong reducing capacities as demonstrated by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 24 publications
(20 reference statements)
2
34
0
Order By: Relevance
“…Some of the S.faecalis and S. faecium strains were atypical in arabinose and melezitose fermentation. Other workers (2) have reported that the fermentation reactions of these two sugars are not always appropriate for the differentiation of S. faecalis from S. faecium.…”
Section: Identification Of Fecal Streptococcimentioning
confidence: 92%
See 2 more Smart Citations
“…Some of the S.faecalis and S. faecium strains were atypical in arabinose and melezitose fermentation. Other workers (2) have reported that the fermentation reactions of these two sugars are not always appropriate for the differentiation of S. faecalis from S. faecium.…”
Section: Identification Of Fecal Streptococcimentioning
confidence: 92%
“…The broth was sterilized filtration and dispensed in 3-ml amounts into test tubes (13 by 100 mm). The methods of growth in 0.1 % methylene blue milk (8), reduction of 2,3,5-triphenyltetrazoliumchloride (TTC) (34), hydrolysis of starch and gelatin (6), polysaccharide (levan or dextran) production from 5% sucrose (6), growth in 0.04% tellurite (34), NHs production from arginine (2), and hydrolysis of hippurate (9) have been described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tests used were selected from those outlined by Smith & Shattock (1962); Deibel, Lake & Niven (1963); Deibel (1964) ;Cowan & Steel (1965); Whittenbury (1965); Sharpe, Fryer & Smith (1966) ;Jones, Sackin & Sneath (1972), and Buchanan & Gibbons (1974). Inocula were prepared from active cultures (24 h old) in yeast-glucose broth (YGB) of the following composition (g/lOO ml): nutrient broth granules (Oxoid no.…”
Section: Examination Of Streptococcimentioning
confidence: 99%
“…The metabolic and nutritional characteristics of the group D streptococci have been widely studied and reviewed by Deibel (1964). The nutrition of Strep.…”
mentioning
confidence: 99%